Russia's military policy in the post-Soviet space: Aims, instruments and perspectives - Margarete Klein (Stiftung Wissenschaft und Politik (SWP), 2019)
Since the Russo-Georgian war and the start of military reform in 2008, the importance of military means in Russia's foreign policy toolbox has increased. This is especially true of the post-Soviet space, where Moscow's vital security interests and regional ambitions converge. Russia is pursuing three goals here: it wants to ward off threats, secure its supremacy over the region and limit the room for manoeuvre of external actors, such as the US, NATO or China. In doing so, it is guided by a three-level approach which consists of strengthening unilateral power projection capabilities and expanding bilateral and multilateral cooperation.The balance of Russian military policy in the post-Soviet space is mixed. It is true that, today, Russia's significantly modernised armed forces can cover a broad spectrum of operations and exert political pressure through a show of force. On the other hand, Moscow's attempt to establish one-sided dependencies through military cooperation has proven to be only partially achievable. As in the political and economic spheres, it is also evident in the military sphere that Russia's desire for a zone of influence clashes with the reality of an increasingly differentiated area. The intervention in Ukraine intensified this trend, as even hitherto close allies of Russia in the CSTO military alliance now show more scepticism in their cooperation with their large neighbour.
Keywords: 320